Building and Codifying the Strategic Agility of Handball Coaches from the Players’ Point View - Reem Abbas Karim; Intisar Owaid (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of the study lies in the extent to which the trainer possesses strategic agility and employs itin his training work. The problem arises in the study of the strategic agility of a handball coach. Researchobjectives: Building and applying the scale of strategic agility for handball coaches from the players’point view, as well as setting standard levels for the scale of strategic agility of handball coaches from theplayers’ point of view, and the researcher used the descriptive approach in the survey method because it ismore appropriate for the objectives of the research and the nature of the problem. The research communityconsists of the Iraqi handball premier league players for the season (2019-2020) of (140) Player, and all theresearch sample was deliberately chosen. The researcher concluded building and codifying the strategicagility scale for handball coaches from the players ’point of view. The research sample was distributed overfive levels of the strategic agility scale for handball coaches from the players’ point of view. Therefore, theresearcher recommends adopting the scale designed for coaches, a tool for measuring the trainers’ possessionof strategic agility.